Vliv covidu-19 na existenci závazku a plnění smluvních povinností - Petr Tomášek; Klára Hurychová (Acta Universitatis Carolinae. Iuridica, 2021)
Several legal provisions respond to a substantial change in circumstances in contractual relationships. The performance of a contract may be impossible initially at the time of contract creation, or, more frequently, may become impossible within the existence of the contract. While the former results in invalidity of the contract itself, the latter leads to a discharge of the obligation created by the contract. However, the impossibility of performance is to be distinguished from such a change in circumstances that merely creates a gross disproportion in the rights and duties of the parties by disadvantaging one of them either by disproportionately increasing the costs of the performance or disproportionately reducing the value of the performance. On this basis, the affected party may seek a renegotiation of the contract and the court may decide to revise the obligation in restoring the balance of rights and duties of the parties.